The development of duodenal microadenomas in FAP patients: the human correlate of the Min mouse. - Preston, S; Leedham, S; Oukrif, D; Deheregoda, M; Goodlad, R; Poulsom, R; Alison, MR; Wright, N; Novelli, M (2008)
UNLABELLED: The morphological changes associated with the adenoma-carcinoma sequence are well documented in the colorectum. Small intestinal carcinogenesis is thought to progress through a similar adenoma-to-carcinoma pathway, but there is a relative dearth of studies examining the associated morphological changes. The best-known mouse model of intestinal neoplasia, the multiple intestinal neoplasia (Min) mouse, has been criticized as a genetic model of intestinal neoplasia, as the majority of its tumours occur in the small intestine. We examined pancreatico-duodenal resection specimens from seven familial adenomatous polyposis (FAP) patients. Serial sections of these were stained with haematoxylin and eosin for beta-catenin and its downstream target CD44, for BMPR1a, lysozyme, carbonic anhydrase II, and with MIB-1. Individual dysplastic crypts were isolated and mutations in the FAP (APC) gene compared between the top and bottom of the crypt. We found that: (a) duodenal microadenomas are extremely common in FAP patients; (b) these grow in the core of duodenal villi, forming lesions similar to those described in the Min mouse; (c) many lesions arise as monocryptal adenomas and grow by a process of crypt fission and branching; (d) migrating adenomatous cells lose their dysplastic phenotype as they migrate up the crypt villous axis; and (e) Paneth cells lose positional information. IN CONCLUSION: (a) the morphological similarity of adenomas in the Min mouse and human suggest the Min mouse is a good model of FAP; (b) duodenal adenomas in FAP originate in monocryptal adenomas and follow the 'bottom-up' rather than the 'top-down' model of morphogenesis; (c) early microadenomas show evidence of cellular differentiation; (d) defects in the positioning of Paneth cells suggests disruption of the EphB2:EphB3 receptor system.